Application of Problem-Solving Method for Understanding Al-Qur’an Memorization Difficulties in Elementary Students - Hasanah, Hikmatul; Nurdiansyah, Nano (Jurnal Keprofesian Guru Keagamaan, 2024)
This research aims to apply the Problem Solving method to overcome the difficulties of fifth grade students at SDN 126 Inpres Kariango in memorizing and understanding the main material of the Al-Quran. This Classroom Action Research (PTK) was carried out through three cycles involving planning, implementation, observation and reflection stages. The research results show that the Problem Solving method is effective in improving students' memorization abilities and deepening their understanding of the meaning of memorized verses. The application of this method also increases students' learning motivation, where students who were previously less motivated become more enthusiastic in memorizing and understanding the Al-Quran. Apart from that, there has been an increase in students' social skills, such as the ability to work together and communicate through group discussions which are part of the Problem Solving process. The implications of this research show that the Problem Solving method can be an effective alternative in learning to memorize the Quran, by providing space for students to think critically, independently, and understand the meaning of the verses in more depth. Teachers also play an important role as facilitators in guiding students in the problem solving process.